Perampanel in real-world clinical care of adolescent and adult patients with epilepsy: Results from the retrospective Phase IV PROVE Study. (May 2022) - Segal, Eric; Wheless, James; Moretz, Katherine; Penovich, Patricia; Patten, Anna; Malhotra, Manoj
Highlights: PROVE was a retrospective, non-interventional phase IV study of perampanel. This analysis evaluated final data from adolescent and adult patients. Perampanel was associated with favorable retention rates and sustained efficacy. No new safety signals were observed with perampanel in adolescent and adult patients. Abstract: Purpose: Report final data from adolescent (12–<18 years) and adult (≥18 years) patients from PROVE (NCT03208660), a multicenter, retrospective, non-interventional, Phase IV study to assess retention, efficacy, safety, and dosing of perampanel in patients with epilepsy during routine clinical care. Methods: Data were retrospectively collected from medical/pharmacy records of patients in the US initiating perampanel after January 1, 2014, according to treating clinicians' recommendation. Retention rate was the primary efficacy endpoint. Secondary endpoints included median percent changes in seizure frequency, seizure-freedom rates, investigator's impression of seizure effect, and treatment-emergent adverse events (TEAEs). Results: The Safety Analysis Set (SAS) included 294 adolescents and 1157 adults (median maximum perampanel dose, 6.0 mg/day). In patients eligible for inclusion in the retention rate analysis, 24-month retention rates were 53.5% ( n =91/170) in adolescents and 47.8% ( n =354/741) in adults. In patients with available efficacy data during Months 10–12, median percent seizure frequency reductions were 79.3% ( n =20) in adolescents and 70.8% ( n =92) in adults. Most patients in the SAS with seizure-effect data experienced an improvement in seizures at the last follow-up time point (adolescents, 51.4% [ n =128/249]; adults, 52.3% [ n =506/967]). TEAEs occurred in 113 adolescents (38.4%; most common, aggression [6.5%]) and 512 adults (44.3%; most common, dizziness [9.2%]). Conclusion: Perampanel demonstrated favorable retention rates and sustained efficacy (up to 2 years) in adolescent and adult patients during routine clinical care; no new safety signals were observed. ClinicalTrials.gov identifier: NCT03208660 (https://clinicaltrials.gov/ct2/show/NCT03208660 ).